Cannabinoid CB1 receptor in dorsal telencephalic glutamatergic neurons drives overconsumption of palatable food and obesity - Ruiz de Azua, Inigo (Neuropsychopharmacology, 2021)
Palatable food can promote overfeeding beyond homeostatic requirements, thereby constituting a major risk to obesity. Here, the lack of cannabinoid type 1 receptor (CB1) in dorsal telencephalic glutamatergic neurons (Glu-CB1-KO) abrogated the overconsumption of palatable food and the development of obesity. On low-fat diet, no genotype differences were observed. However, under palatable food conditions, Glu-CB1-KO mice showed decreased body weight and food intake. Notably, Glu-CB1-KO mice were protected from alterations in the reward system after high-fat diet feeding. Interestingly, obese wild-type mice showed a superior olfactory detection as compared to mutant mice, suggesting a link between overconsumption of palatable food and olfactory function. Reconstitution of CB1 expression in olfactory cortex in high-fat diet-fed Glu-CB1-KO mice using viral gene delivery partially reversed the lean phenotype concomitantly with improved odor perception. These findings indicate that CB1 in cortical glutamatergic neurons regulates hedonic feeding, whereby a critical role of the olfactory cortex was uncovered as an underlying mechanism.